2017
DOI: 10.1158/1078-0432.ccr-16-0235
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Total Lesion Glycolysis by 18F FDG PET/CT Significantly Improves Prognostic Value of GEP and ISS in Myeloma

Abstract: Introduction Fluorine-18 fluorodexyglucose positron emission tomography with CT attenuation correction (18F-FDG PET/CT) is useful in the detection and enumeration of focal lesions and in semi-quantitative characterization of metabolic activity (glycolytic phenotype) by calculation of glucose uptake. Total lesion glycolysis (TLG) and metabolic tumor volume (MTV) have the potential to improve the value of this approach and enhance the prognostic value of disease burden measures. This study aims to determine whet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
84
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 19 publications
5
84
0
Order By: Relevance
“…Several studies have suggested a higher sensitivity of 11 C-MET PET/CT over 18 F-FDG PET/CT in the detection of both intra-and extramedullary disease [18,19]. In addition, a better correlation of 11 C-MET uptake with the degree of BM infiltration by malignant PCs has been recently reported [20].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have suggested a higher sensitivity of 11 C-MET PET/CT over 18 F-FDG PET/CT in the detection of both intra-and extramedullary disease [18,19]. In addition, a better correlation of 11 C-MET uptake with the degree of BM infiltration by malignant PCs has been recently reported [20].…”
Section: Introductionmentioning
confidence: 99%
“…On top of this, post-therapy imaging studies have demonstrated that PET negativity after induction treatment [6,7] or autologous/allogeneic stem cell transplantation (ASCT) [7][8][9][10] correlates with longer progression-free survival (PFS). Moreover, new parameters measuring tumor burden in 18 F-FDG PET/CT such as metabolic tumor volume (MTV) and total lesion glycolysis (TLG) have also demonstrated an association with survival in MM patients [11,12]. Furthermore, patients with high TLG had poor outcome even in the context of molecularly defined low-risk disease, highlighting the additional value of novel markers in the assessment of MM.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…FDG PET/CT provide prognostic information in patients with newly diagnosed MM: The presence of a diffuse pattern with MRI, extramedullary disease, the number of FLs, and/or [ 18 F]FDG-avid lesions are associated with shorter survival. [8][9][10][11][12][13][14][15] Based on its ability to indicate metabolic activity, [ 18 F]FDG is the preferred and widely used tracer for PET/CT 1 ; however, the sensitivity of [ 18…”
mentioning
confidence: 99%